Effects of Different Light Sources on Neural Activity of the Paraventricular Nucleus in the Hypothalamus - Michio Yokoyama (Medicina, 2019)
Background and Objectives: Physical function is influenced by light irradiation, and interest in the influence of light irradiation on health is high. Light signals are transmitted from the retina to the suprachiasmatic nucleus (SCN) via the retinal hypothalamic tract as non-image vision. Additionally, the SCN projects a nerve to the paraventricular nucleus (PVN) which acts as a stress center. This study examined the influences of three different light sources on neural activity in the PVN region using two different color temperatures. Materials and Methods: Experiments were conducted using twenty-eight Institute of Cancer Research (ICR) mice (10 week old males). Three light sources were used: (1) organic light-emitting diode (OLED) lighting, (2) LED lighting, and (3) fluorescent lighting. We examined the effects of light irradiation from the three light sources using two different color temperatures (2800 K and 4000 K). Perfusion was done 60 min after light irradiation, and then the brain was removed from the mouse for an immunohistochemistry analysis. c-Fos was immunohistochemically visualized as a marker of neural activity in the PVN region. Results: The number of c-Fos-positive cells was found to be significantly lower under OLED lighting and LED lighting conditions than under fluorescent lighting at a color temperature of 2800 K, and significantly lower under OLED lighting than LED lighting conditions at a color temperature of 4000 K. Conclusions: This study reveals that different light sources and color temperatures alter the neural activity of the PVN region. These results suggest that differences in the light source or color temperature may affect the stress response.